2021
DOI: 10.3389/fcell.2021.667684
|View full text |Cite
|
Sign up to set email alerts
|

Functions and Mechanisms of Lysine Glutarylation in Eukaryotes

Abstract: Lysine glutarylation (Kglu) is a newly discovered post-translational modification (PTM), which is considered to be reversible, dynamic, and conserved in prokaryotes and eukaryotes. Recent developments in the identification of Kglu by mass spectrometry have shown that Kglu is mainly involved in the regulation of metabolism, oxidative damage, chromatin dynamics and is associated with various diseases. In this review, we firstly summarize the development history of glutarylation, the biochemical processes of glut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 92 publications
(201 reference statements)
0
11
0
Order By: Relevance
“…We first performed whole protein lysate western blot analysis with a pan-lysine-glutarylation (K-glu) antibody (Tan et al ., 2014; Xie et al ., 2021) and found that glutarylation is clearly detectable in CD8 + T cells (Figure 4B). We also found that glutarylation patterns change strikingly upon CD8 + T cell activation (Figure 4B).…”
Section: Resultsmentioning
confidence: 99%
“…We first performed whole protein lysate western blot analysis with a pan-lysine-glutarylation (K-glu) antibody (Tan et al ., 2014; Xie et al ., 2021) and found that glutarylation is clearly detectable in CD8 + T cells (Figure 4B). We also found that glutarylation patterns change strikingly upon CD8 + T cell activation (Figure 4B).…”
Section: Resultsmentioning
confidence: 99%
“…34,35 Lysine (K) glutarylation is known to be associated with cellular functions such as metabolic processes, oxidative damage, and other mitochondrial functions. 36,37 We identified 1058 unique glutarylation sites mapping to 836 proteins in this study. The examples include several proteins of the early transcribed membrane protein (ETRAMP) family, including erythrocyte membrane protein 3 (PY05500 at K15, PY04042 at K863, PY06125 at K770), erythrocyte membrane-associated antigen (PY06959 at K460), erythrocyte membrane-associated antigen, putative (PY06110 at K125), and ETRAMP (PY00205 at K17).…”
Section: ■ Resultsmentioning
confidence: 99%
“… 491 SIRT5 defects lead to an increase in succinyl‐coA in the heart. 504 Elevated levels of Ksucc can lead to hypertrophic obstructive cardiomyopathy, 528 while oxidative stress caused by Kglu may be an important mechanism for inducing CVDs. 546 A high‐fat diet causes adverse effects on cardiovascular health, especially under stressful conditions.…”
Section: Other Scfa Modificationsmentioning
confidence: 99%
“…Kglu, a reversible, dynamic and conserved modification, is produced by covalently binding glutaryl groups to lysine residues 504 and occurs mainly in mitochondria 532 . Kglu plays an important role in regulating protein structural changes, 532 oxidative damage, 533 mitochondrial functions, 534 and sperm motility 535 …”
Section: Other Scfa Modificationsmentioning
confidence: 99%